Cerita Rakyat Daerah Pegunungan Kabupaten Karanganyar (Analisis Struktur Naratif dan Fungsi Menurut Alan Dundes) - Oktivisari, Adestya Tahira; Wijaya, Fasyeh Paramasari; Khoiriyati, Hesti Nabilla; Marfuah, Putri Aprihlia Tul (Universitas Sebelas Maret, 2024)
Oral literature research on “Dumadine Candi Sukuh” and “Pertapan Cokro Kembang” aims to find out and analyze the series of motifs and functions based on Alan Dundes' theory. The existence of this research is also relevant to the absence of analysis of folklore in the Karanganyar area because mountainous areas are indeed difficult for researchers to reach. This research uses data analysis methods in the form of motifs and folklore functions based on Alan Dundes' theory using data in the form of words and texts. The data acquisition is taken through data collection techniques in the form of interviews, personal notes, photos, and other documents. The results showed that the folklore of “Dumadine Candi Sukuh” and “Pertapan Cokro Kembang” has five dominant motifs, namely 1) lack liquidate, 2) lack, 3) task, 4) task completed, and 5) consequence. Then, function is as 1) an educational tool, 2) increasing the solidarity of a group, 3) sanctions for people to behave well, 4) solace, and 5) social criticism. So it can be concluded that oral literature research on “Dumadine Candi Sukuh” and “Pertapan Cokro Kembang” both have complex storylines.